Endogenous group formation in experimental contests - Luisa Herbst; Kai A. Konrad; Florian Morath (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
We study endogenous group formation in tournaments employing experimental three-player contests. We find that players in endogenously formed alliances cope better with the moral hazard problem in groups than players who are forced into an alliance. Also, players who are committed to expending effort above average choose to stand alone. If these players are forced to play in an alliance, they invest even more, whereas their co-players choose lower effort. Anticipation of this exploitation may explain their preference to stand alone.
urn:nbn:de:bvb:19-epub-17245-1
Keywords: D72; D74; 330; Endogenous group formation; contest; conflict; alliance; experiment; moral hazard problem; free-riding; in-group favoritism